Adaptive resource allocation in multimodal activity networks - Tereso, Anabela Pereira (2004)
In practice, project managers must cope with uncertainty, and must manipulate the allocation of their resources adaptively in order to achieve their ultimate objectives. Yet, treatments of the well-known ‘resource constrained project scheduling problem’ have been deterministic and static, and have addressed mostly unimodal activities. We present an approach to resource allocation under stochastic conditions for multimodal activity networks. Optimization is via dynamic programming, which proves to be demanding computationally. We suggest approximation schemes that do not detract signi…cantly from optimality, but are modest in their computational requirements.